11 см
Пошаговое объяснение:
1) 3 3/5 - 1 7/10 = 3 6/10 - 1 7/10 = 2 16/10 - 1 7/10 = 1 9/10 (см) - ширина
2) 2 * (3 3/5 + 1 9/10) =
2 * (3 6/10 + 1 9/10) =
2 * 4 15/10 = 2 * 55/10 =
110/10 = 11 (см) - периметр
Но это может быть не правильным
3.3/5- 17/10 =1.9/10
3.3/5+1.9/10=5.1/2
51/2*2=11
11 см
Пошаговое объяснение:
1) 3 3/5 - 1 7/10 = 3 6/10 - 1 7/10 = 2 16/10 - 1 7/10 = 1 9/10 (см) - ширина
2) 2 * (3 3/5 + 1 9/10) =
2 * (3 6/10 + 1 9/10) =
2 * 4 15/10 = 2 * 55/10 =
110/10 = 11 (см) - периметр
Пошаговое объяснение:
Но это может быть не правильным
3.3/5- 17/10 =1.9/10
3.3/5+1.9/10=5.1/2
51/2*2=11